Design and Build Risk Management Model for Pork Supply Chain in North Sulawesi - Endoh, Eusebius K.M.; Lainawa, Jolyanis (AIBPM Publisher, 2024)
This study aims to design a pork supply chain risk management model. This model is composed of four main models, namely; (1) risk identification model, (2) risk assessment model, (3) risk mitigation model and (4) pork price calculation model at the farm level by incorporating risk factors. Model 1, risk identification is divided into two sub-models, namely the supply chain risk mapping model in each supply chain network and the risk mapping model in pork delivery activities. Model 2, the risk assessment model, is divided into three sub-models, namely the risk measurement model, the risk relationship chain model and the risk performance model. Furthermore, model 3, namely risk mitigation is determined based on risk evaluation and risk consequences of the risk relationship chain that has the highest risk magnitude. While model 4, designs a risk assessment system and calculates the price of pork at the risk-based farm level.